2012
DOI: 10.1002/prot.24092
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the reconstruction of macromolecular assemblies with toleranced models

Abstract: We introduce toleranced models (TOMs), a generic and versatile framework meant to handle models of macromolecular assemblies featuring uncertainties on the shapes and the positions of proteins. A TOM being a continuum of nested shapes, the inner (resp. outer) ones representing high (low) confidence regions, we present topological and geometric statistics assessing features of this continuum at multiple scales. While the topological statistics qualify contacts between instances of protein types and complexes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Our TOM of the NPC being based on the average model from, which involves 16 copies of the Y ‐complex, we could not carry out any evaluation of the fence‐like model. However, our analysis of the Y ‐complex based on the Hasse diagram was globally consistent with an organization in two rings (first model) . Here again, one should be aware of the fact that the TOM being derived from the model proposed by, it relies on the initial datasets used to generate this averaged model.…”
Section: Methodssupporting
confidence: 62%
See 2 more Smart Citations
“…Our TOM of the NPC being based on the average model from, which involves 16 copies of the Y ‐complex, we could not carry out any evaluation of the fence‐like model. However, our analysis of the Y ‐complex based on the Hasse diagram was globally consistent with an organization in two rings (first model) . Here again, one should be aware of the fact that the TOM being derived from the model proposed by, it relies on the initial datasets used to generate this averaged model.…”
Section: Methodssupporting
confidence: 62%
“…The quantitative exploitation of such maps, and the analysis of their coherence with respect to various experimental data motivated the development of toleranced models (TOM), whose main features are recalled now.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data showed that docking of even highly inaccurate protein models (~6 Å RMSD from the X-ray structure) still yields structurally meaningful results, accurate enough to predict binding interfaces and to serve as starting points for further structural analysis. The utility of the modeled proteins in protein–protein docking was further demonstrated by other systematic studies, involving docking approaches based on computational geometry [31,32] validated on benchmark protein–protein sets [31] and the nuclear pore complex [32], and Rosetta-based docking of antibody–antigen homology models [33]. The template-based docking approaches increasingly focus on the modeled structures as part of the docking protocol [34,35•] or the subject of structural alignment [36••,37••].…”
Section: Docking Of Modelsmentioning
confidence: 97%
“…In the context of RDI, the models stemming from such analysis do not, in general, achieve atomic resolution. They can, however, be used to bridge the gap to atomic level models of subsystems of the assembly under scrutiny (9,10).…”
Section: Connectivity Inference From Sets Of Oligomersmentioning
confidence: 99%